Smooth quartzite plate with soft touch feeling and manufacturing process of smooth quartzite plate
By using alumina and ultra-high molecular weight polyethylene as the modified layer in quartz stone slabs, combined with the improvement of glass fiber and acrylic resin, the problem of poor surface performance of existing quartz stone slabs is solved, achieving a smooth and soft touch. The surface improves wear resistance and impact resistance, ensuring the aesthetics and durability of the board.
Patent Information
- Application Number
- CN202411370163.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2025-01-07
AI Technical Summary
The polishing depth of existing quartz stone slabs is shallow, resulting in poor surface performance and insufficient wear and compressive performance, which affects its application and aesthetics.
Alumina and ultra-high molecular weight polyethylene are used as modified layers to prepare modified resins by high-frequency high-voltage corona discharge treatment and melt spinning method, combining glass fibers and acrylic resins to improve the wear resistance and impact strength of the sheets. , and through specific process steps such as high-temperature curing and low-temperature curing, a smooth and soft touch surface is formed.
It significantly improves the wear resistance and impact resistance of quartz stone sheets, making their surface smooth and smooth, can effectively resist wear during use, and maintain aesthetics and durability.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of plate manufacturing, in particular to a quartz stone plate which is smooth and has a soft touch, and also to a manufacturing process of the quartz stone plate. Background Art
[0002] Quartz slabs are widely used in public places such as hospitals, exhibitions, laboratories, as well as kitchen countertops, washbasins, kitchen and bathroom walls in home decoration. They are a new type of environmentally friendly and green building interior decoration material that is non-radioactive and reusable. Quartz slabs are a new type of stone material, mainly artificially synthesized by more than 90% quartz crystals plus resin and other trace elements. Its main material is quartz, a mineral that easily turns into liquid when heated or pressurized. In addition to the main quartz sand and quartz powder, the synthetic raw materials of quartz slabs also include unsaturated polyester resin, glass particles, color paste, curing agent and coupling agent. These raw materials are pressed into large-sized slabs by special machines under specific physical and chemical conditions.
[0003] The existing quartz stone slabs have a shallow grinding depth, which results in poor polishing operability, affecting the surface performance of the quartz stone slab products. In addition, the overall wear resistance and compression resistance of the slabs are poor, which is not conducive to promotion and use. Summary of the invention
[0004] In view of the above-mentioned shortcomings of the prior art, the purpose of the present invention is to provide a smooth and soft-touch quartz stone slab and its manufacturing process, so as to produce a quartz stone slab with a smooth and flat surface and a soft touch, which can effectively resist wear during use and maintain beauty and durability.
[0005] A quartz plate with a smooth and soft touch, the quartz plate comprises the following components: the quartz sand, quartz powder, alumina, ultra-high molecular weight polyethylene, modified resin and additives are prepared in a certain proportion to obtain the quartz plate; wherein the modified resin is prepared by blending glass fiber and acrylic resin in a ratio of 1:7-9.
[0006] In one embodiment, the auxiliary agent is prepared by mixing white paste, curing agent and coupling agent in a ratio of 1:2 to 3:1 to 2.
[0007] Furthermore, the curing agent is any one of vinyltriamine, diaminocyclohexane, methylenebiscyclohexylamine, ethylenediamine, diethylenetriamine and benzidine; and the coupling agent is KH550, KH560, KH570, KH792, DL602 or DL171.
[0008] In one of the embodiments, the quartz stone plate is composed of the following by weight: 15% to 22% quartz sand, 22% to 30% quartz powder, 20% to 35% alumina, 2% to 8% ultra-high molecular weight polyethylene, 12% to 23% modified resin, and 2% to 4% additives.
[0009] Furthermore, the mass composition of the quartz stone plate is as follows: 20% quartz sand, 25% quartz powder, 30% alumina, 5% ultra-high molecular weight polyethylene, 17% modified resin, and 3% additives.
[0010] Furthermore, the polymer solid content of the modified resin is ≥80%, and the viscosity is 1100-1300 Mpa.s;
[0011] The method for preparing the modified resin is specifically performed as follows:
[0012] Step 1: Mix the glass fiber with 80% by mass sulfuric acid solution and 90% by mass nitric acid solution, and stir evenly to obtain a mixed solution;
[0013] Step 2: Mix the mixed solution and acrylic resin, add anhydrous ethanol, and perform ultrasonic treatment at 400-700W for 1-2h;
[0014] Step 3: Continue to add silane coupling agent and deionized water, stir at a speed of 200-500 rpm for 30-40 minutes, add pH adjuster to adjust the pH of the solution to 7-8, and obtain modified resin.
[0015] Furthermore, the weight ratio of the sulfuric acid solution to the nitric acid solution is 1:0.5-1; the weight ratio of the silane coupling agent to deionized water is 0.1-0.3:1.
[0016] In one embodiment, the ultra-high molecular weight polyethylene is produced by melt spinning;
[0017] The melt spinning method is used to prepare ultra-high molecular weight polyethylene, and the specific operation process is as follows:
[0018] Step 1: removing impurities from ultra-high molecular weight polyethylene powder;
[0019] Step 2: After removing impurities, cool to 0-20°C, put into a melter, and melt polymerize at 200-300°C and 2-3MPa. Finally, extrude the melt through an extruder to obtain ultra-high molecular weight polyethylene.
[0020] A process for producing a quartz stone plate, which is used to produce the smooth and soft-touch quartz stone plate, comprising the following processing steps:
[0021] S1: placing aluminum oxide into a processing device and applying high-frequency high-voltage electricity to cause corona discharge, and then adding ultra-high molecular weight polyethylene to obtain a mixture for standby use;
[0022] S2: Mix quartz sand, quartz powder, modified resin, white slurry, curing agent and coupling agent, transfer to a pressing machine for pressing and molding, and then cure at a medium temperature of 80-120° C. to obtain a green body layer;
[0023] S3: applying the mixture to the sheet material layer, coating the color slurry and filling the fine lines, and then performing low temperature curing treatment to obtain a cured material;
[0024] S4 polishes the solidified material to obtain a quartz stone plate.
[0025] In one embodiment, the pressing pressure is 20-50 MPa; the amount of the mixture applied to the sheet blank layer is 280-300 g / m 2 The low temperature curing is carried out in a pipeline curing furnace, and the curing temperature is 75-85°C.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] Glass fiber is introduced into acrylic resin to improve the resin and add glass fiber to increase the flexural strength, thereby achieving the purpose of improving the mechanical properties of quartz stone slabs and increasing the impact strength of quartz stone slabs.
[0028] Alumina and ultra-high molecular weight polyethylene are co-doped and modified to improve the wear resistance of quartz stone plates, and the overall impact resistance of the plates is improved by synergistic cooperation. Alumina and ultra-high molecular weight polyethylene are used as modified layers and applied to the plate blank. Alumina is used to produce a greater grinding depth, making the surface of the quartz stone plate smooth and flat with a soft touch. When the plate is used, it can effectively resist wear during use and maintain beauty and durability. DETAILED DESCRIPTION
[0029] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with the embodiments. Additional aspects and advantages of the present invention will be given in part in the following description, and will become apparent from the following description, or will be understood through the practice of the present invention. It should be understood that the following description is only used to explain the present invention and is not intended to limit the present invention.
[0030] As used herein, the terms "comprises," "including," "contains," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.
[0031] When an amount, concentration, or other value or parameter is expressed as a range, a preferred range, or a range limited by a series of upper preferred values and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including a range of "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5" etc. When a numerical range is described in this article, unless otherwise specified, the range is intended to include its end values and all integers and fractions within the range.
[0032] The specific embodiments of the present invention are described in detail below.
[0033] Example 1
[0034] This embodiment provides a quartz stone plate that is smooth and has a soft touch, which has the following components: the quartz sand, quartz powder, alumina, ultra-high molecular weight polyethylene, modified resin and additives are prepared in a certain proportion to obtain the quartz stone plate.
[0035] The auxiliary agent is prepared by mixing white pulp, vinyl triamine and coupling agent KH550 in a ratio of 1:2:1. In this embodiment, the white pulp plays a role in adjusting the color of the board, the vinyl triamine plays a role in adjusting the curing process of the board, and the coupling agent KH550 plays a role in improving the interface performance between various components and enhancing the overall performance of the board.
[0036] The mass composition of the quartz stone plate is as follows: 18% quartz sand, 26% quartz powder, 30% alumina, 6% ultra-high molecular weight polyethylene, 16% modified resin, and 4% additives. The fineness of the quartz powder is 325 meshes, and the whiteness is ≥95 degrees to ensure the quality and performance of the plate. In this embodiment, quartz sand and quartz powder cooperate to form the basic skeleton of the plate. It should be noted that in order to ensure the quality and performance of the plate, quartz sand with uniform particles, no impurities and no foreign matter is used.
[0037] The modified resin is prepared by mixing glass fiber and acrylic resin in a ratio of 1:7. The polymer solid content of the modified resin is ≥80%, and the viscosity is 1100 Mpa.s. The modified resin is used to combine quartz sand and quartz powder well, thereby enhancing the durability and stability of the quartz stone plate.
[0038] In this embodiment, the acrylic resin is modified by introducing glass fibers into the resin, and the flexural strength is increased by adding the glass fibers, thereby achieving the purpose of improving the mechanical properties of the quartz stone plate and increasing the impact strength of the quartz stone plate.
[0039] The method for preparing the modified resin is specifically performed as follows:
[0040] Step 1: Mix the glass fiber with a sulfuric acid solution having a mass fraction of 80% and a nitric acid solution having a mass fraction of 90%, and stir evenly to obtain a mixed solution; the weight ratio of the sulfuric acid solution to the nitric acid solution is 1:0.5.
[0041] Step 2: Mix the mixed liquid and acrylic resin, add anhydrous ethanol, and perform ultrasonic treatment at 400W for 2h to make the glass fiber evenly dispersed in the acrylic resin.
[0042] Step 3: Continue to add silane coupling agent and deionized water, stir at a speed of 200 rpm for 40 minutes, add a pH adjuster to adjust the pH of the solution to 7, and obtain a modified resin; the mass ratio of the silane coupling agent to deionized water is 0.3:1.
[0043] The ultra-high molecular weight polyethylene is produced by melt spinning, and the specific operation process is as follows:
[0044] Step 1: remove impurities from the ultra-high molecular weight polyethylene powder. The impurity removal process includes cleaning, dust removal and drying. The drying process is carried out in a reactor at a drying temperature of 50° C. and a drying time of 4 hours. In this embodiment, surface impurities and dust are removed based on dust removal to ensure the purity of the raw materials, and after dust removal, drying is performed to remove moisture.
[0045] Step 2: After removing impurities, cool to 20°C, then put into a melting machine, melt polymerize at 200°C and 2MPa to obtain ultra-high molecular weight polyethylene. In this embodiment, alumina and ultra-high molecular weight polyethylene are co-doped and modified to improve the wear resistance of the quartz stone plate, and the overall impact resistance of the plate is improved by synergistic cooperation. Alumina and ultra-high molecular weight polyethylene are used as modified layers and applied to the plate blank. Alumina is used to produce a greater grinding depth, so that the surface of the quartz stone plate is smooth and flat with a soft touch. When the plate is used, it can effectively resist wear during use and maintain beauty and durability.
[0046] Example 2
[0047] This embodiment provides a smooth and soft-touch quartz plate, which has the following components: the quartz sand, quartz powder, alumina, ultra-high molecular weight polyethylene, modified resin and additives are prepared in a certain proportion to obtain the quartz plate. Among them, the modified resin is prepared by mixing glass fiber and acrylic resin in a ratio of 1:8.
[0048] The auxiliary agent is prepared by mixing white paste, diaminocyclohexane and coupling agent KH560 in a ratio of 1:2:2. In this embodiment, the white paste plays a role in adjusting the color of the board, the diaminocyclohexane plays a role in adjusting the curing process of the board, and the coupling agent KH560 plays a role in improving the interface performance between various components and enhancing the overall performance of the board.
[0049] The mass composition of the quartz stone plate is as follows: 20% quartz sand, 25% quartz powder, 30% alumina, 5% ultra-high molecular weight polyethylene, 17% modified resin, and 3% additives. The fineness of the quartz powder is 360 meshes, and the whiteness is ≥95 degrees to ensure the quality and performance of the plate. In this embodiment, quartz sand and quartz powder cooperate to form the basic skeleton of the plate. It should be noted that in order to ensure the quality and performance of the plate, quartz sand with uniform particles, no impurities and no foreign matter is used.
[0050] The modified resin has a polymer solid content of ≥80% and a viscosity of 1200 Mpa.s. The modified resin is used to combine quartz sand and quartz powder well, thereby enhancing the durability and stability of the quartz stone slab.
[0051] In this embodiment, the acrylic resin is modified by introducing glass fibers into the resin, and the flexural strength is increased by adding the glass fibers, thereby achieving the purpose of improving the mechanical properties of the quartz stone plate and increasing the impact strength of the quartz stone plate.
[0052] The method for preparing the modified resin is specifically performed as follows:
[0053] Step 1: Mix the glass fiber with a sulfuric acid solution having a mass fraction of 80% and a nitric acid solution having a mass fraction of 90%, and stir evenly to obtain a mixed solution; the weight ratio of the sulfuric acid solution to the nitric acid solution is 1:0.8.
[0054] Step 2: Mix the mixed liquid and acrylic resin, add anhydrous ethanol, and perform ultrasonic treatment at 600W for 1.5h to make the glass fiber evenly dispersed in the acrylic resin.
[0055] Step 3: Continue to add silane coupling agent and deionized water, stir at a speed of 400 rpm for 35 minutes, add a pH adjuster to adjust the pH of the solution to 8, and obtain a modified resin; the mass ratio of the silane coupling agent to deionized water is 0.2:1.
[0056] The ultra-high molecular weight polyethylene is produced by melt spinning, and the specific operation process is as follows:
[0057] Step 1: The ultra-high molecular weight polyethylene powder is subjected to impurity removal treatment. The impurity removal treatment includes cleaning, dust removal and drying. The drying treatment is carried out in a reactor at a drying temperature of 90° C. and a drying time of 3 hours. In this embodiment, the surface impurities and dust are removed based on dust removal to ensure the purity of the raw materials, and the dust removal is followed by drying to remove moisture.
[0058] Step 2: After removing impurities, cool to 10°C, then put into a melting machine, melt polymerize at 200°C and 3MPa to obtain ultra-high molecular weight polyethylene. In this embodiment, alumina and ultra-high molecular weight polyethylene are co-doped and modified to improve the wear resistance of the quartz stone plate, and the overall impact resistance of the plate is improved by synergistic cooperation. Alumina and ultra-high molecular weight polyethylene are used as modified layers and applied to the plate blank. Alumina is used to produce a greater grinding depth, so that the surface of the quartz stone plate is smooth and flat with a soft touch. When the plate is used, it can effectively resist wear during use and maintain beauty and durability.
[0059] Example 3
[0060] This embodiment provides a smooth and soft-touch quartz plate, which has the following components: the quartz sand, quartz powder, alumina, ultra-high molecular weight polyethylene, modified resin and additives are prepared in a certain proportion to obtain the quartz plate. Among them, the modified resin is prepared by mixing glass fiber and acrylic resin in a ratio of 1:9.
[0061] The auxiliary agent is prepared by mixing white paste, ethylenediamine and coupling agent DL602 in a ratio of 1:3:2. In this embodiment, the white paste plays a role in adjusting the color of the board, the ethylenediamine plays a role in adjusting the curing process of the board, and the coupling agent DL602 plays a role in improving the interface performance between various components and enhancing the overall performance of the board.
[0062] The mass composition of the quartz stone plate is as follows: 22% quartz sand, 25% quartz powder, 28% alumina, 5% ultra-high molecular weight polyethylene, 17% modified resin, and 3% additives. The fineness of the quartz powder is 400 meshes, and the whiteness is ≥95 degrees to ensure the quality and performance of the plate. In this embodiment, quartz sand and quartz powder cooperate to form the basic skeleton of the plate. It should be noted that in order to ensure the quality and performance of the plate, quartz sand with uniform particles, no impurities and no foreign matter is used.
[0063] The modified resin has a polymer solid content of ≥80% and a viscosity of 1300 Mpa.s. The modified resin is used to combine quartz sand and quartz powder well, thereby enhancing the durability and stability of the quartz stone plate. In this embodiment, the resin is modified by introducing glass fiber into the acrylic resin, and the flexural strength is increased by adding glass fiber, thereby achieving the purpose of improving the mechanical properties of the quartz stone plate and improving the impact strength of the quartz stone plate.
[0064] The method for preparing the modified resin is specifically performed as follows:
[0065] Step 1: Mix the glass fiber with a sulfuric acid solution having a mass fraction of 80% and a nitric acid solution having a mass fraction of 90%, and stir evenly to obtain a mixed solution. The weight ratio of the sulfuric acid solution to the nitric acid solution is 1:1.
[0066] Step 2: Mix the mixed solution and acrylic resin, add anhydrous ethanol, and perform ultrasonic treatment at 700W for 1h to make the glass fiber evenly dispersed in the acrylic resin.
[0067] Step 3: Continue to add silane coupling agent and deionized water, stir at a speed of 500 rpm for 30 minutes, add pH adjuster to adjust the pH of the solution to 8, and obtain modified resin. The mass ratio of the silane coupling agent to deionized water is 0.1-1.
[0068] The ultra-high molecular weight polyethylene is produced by melt spinning, and the specific operation process is as follows:
[0069] Step 1: The ultra-high molecular weight polyethylene powder is subjected to impurity removal treatment. The impurity removal treatment includes cleaning, dust removal and drying. The drying treatment is carried out in a reactor at a drying temperature of 100° C. and a drying time of 2 hours. In this embodiment, the surface impurities and dust are removed based on dust removal to ensure the purity of the raw materials, and the dust removal is followed by drying to remove moisture.
[0070] Step 2: After removing impurities, cool to 0°C, then put into a melting machine, melt polymerize at 300°C, 3MPa to obtain ultra-high molecular weight polyethylene. In this embodiment, alumina and ultra-high molecular weight polyethylene are co-doped and modified to improve the wear resistance of the quartz stone plate, and the overall impact resistance of the plate is improved by synergistic cooperation. Alumina and ultra-high molecular weight polyethylene are used as modified layers and applied to the plate blank. Alumina is used to produce a greater grinding depth, so that the surface of the quartz stone plate is smooth and flat with a soft touch. When the plate is used, it can effectively resist wear during use and maintain beauty and durability.
[0071] Example 4
[0072] This embodiment provides a process for producing a quartz stone plate, which is used to produce a smooth and soft-touch quartz stone plate as described in any one of Embodiments 1 to 3. It should be noted that the process of this embodiment can also be applied to the production of quartz bricks. The process includes the following processing steps:
[0073] S1 puts the aluminum oxide into a processing device and applies high-frequency high-voltage electricity to make it corona discharge, then adds ultra-high molecular weight polyethylene to obtain a mixture for standby use. In this embodiment, the polar group hydroxyl group in the aluminum oxide is introduced into the polyethylene by corona discharge treatment, so that the ultra-high molecular weight polyethylene is dispersed and wrapped on the aluminum oxide, with good compatibility and synergistic cooperation, which enhances the wear resistance of the prepared plate and improves the impact resistance.
[0074] S2: Quartz sand, quartz powder, modified resin, white paste, curing agent and coupling agent are mixed, transferred to a press machine for pressing and molding, and then cured at 100° C. to obtain a green body layer. The pressing pressure is 50 MPa.
[0075] S3: Apply the mixture to the sheet blank layer, coat it with colored slurry and fill the fine lines, then perform low temperature curing to obtain a cured material. The amount of the mixture applied to the sheet blank layer is 300 g / m 2 The low temperature curing is carried out in a pipeline curing furnace, and the curing temperature is 80°C.
[0076] S4 polishes the solidified material to obtain a quartz stone slab with an effect close to that of natural stone.
[0077] Comparative Example 1
[0078] The difference between Comparative Example 1 and Example 2 is that no alumina is added.
[0079] Comparative Example 2
[0080] The difference between Comparative Example 2 and Example 2 is that no ultra-high molecular weight polyethylene is added.
[0081] Comparative Example 3
[0082] The difference between Comparative Example 3 and Example 2 is that acrylic resin is used instead of modified resin.
[0083] The quartz stone plates of Examples 1 to 3 and Comparative Examples 1 to 3 were subjected to touch tests, wear resistance tests and impact strength tests respectively. The specific test process is not described in detail. The test results are shown in Table 1.
[0084] Table 1:
[0085] Touch Wear resistance (rotation) Impact strength(MPa) Example 1 Smooth, soft and non-greasy 6260 142 Example 2 Smooth, soft and non-greasy 6350 159 Example 3 Smooth, soft and non-greasy 6270 148 Comparative Example 1 Flat, rough, greasy 5530 130 Comparative Example 2 Smooth, non-slip, non-greasy 5850 137 Comparative Example 3 Smooth, non-slip, non-greasy 5790 139
[0086] It can be seen from the comparative analysis of Table 1 that the quartz stone plate of the present invention has a soft touch, and the wear resistance and impact resistance of the quartz stone plate can be significantly enhanced by co-doping modification of alumina and ultra-high molecular weight polyethylene.
[0087] The present invention introduces glass fiber into acrylic resin to improve the resin, and adds glass fiber to improve the flexural strength, thereby achieving the purpose of improving the mechanical properties of quartz stone plates and improving the impact strength of quartz stone plates. Alumina and ultra-high molecular weight polyethylene are co-doped and modified to improve the wear resistance of quartz stone plates, and the overall impact resistance of the plates is improved in synergy. Alumina and ultra-high molecular weight polyethylene are used as modified layers and applied to the plate blank. Alumina is used to produce a greater grinding depth, so that the surface of the quartz stone plate is smooth and flat with a soft touch. When the plate is used, it can effectively resist wear during use and maintain beauty and durability.
[0088] The above embodiments are merely preferred implementations of the present invention. Any simple modification, amendment and substitution of the above embodiments based on the technical essence of the present invention shall fall within the scope of the technical solution of the present invention.
Claims
1. A smooth and soft-touch quartz stone plate, characterized in that: The quartz stone plate has the following components: the quartz sand, quartz powder, alumina, ultra-high molecular weight polyethylene, modified resin and additives are prepared in a certain proportion to obtain the quartz stone plate; wherein the modified resin is prepared by blending glass fiber and acrylic resin in a ratio of 1:7-9.
2. The smooth and soft-touch quartz stone plate according to claim 1, characterized in that: The auxiliary agent is prepared by mixing white paste, curing agent and coupling agent in a ratio of 1:2 to 3:1 to 2.
3. The smooth and soft-touch quartz stone plate according to claim 2, characterized in that: in, The curing agent is any one of vinyltriamine, diaminocyclohexane, methylenebiscyclohexaneamine, ethylenediamine, diethylenetriamine and benzidine; The coupling agent is KH550, KH560, KH570, KH792, DL602 or DL171.
4. The smooth and soft-touch quartz stone plate according to claim 1, characterized in that: The mass composition of the quartz stone plate is as follows: 15% to 22% of quartz sand, 22% to 30% of quartz powder, 20% to 35% of alumina, 2% to 8% of ultra-high molecular weight polyethylene, 12% to 23% of modified resin, and 2% to 4% of additives.
5. The smooth and soft-touch quartz stone plate according to claim 4, characterized in that: The mass composition of the quartz stone plate is as follows: 20% of quartz sand, 25% of quartz powder, 30% of alumina, 5% of ultra-high molecular weight polyethylene, 17% of modified resin and 3% of auxiliary agent.
6. The smooth and soft-touch quartz stone plate according to claim 5, characterized in that: The polymer solid content of the modified resin is ≥80%, and the viscosity is 1100-1300 Mpa.s; The method for preparing the modified resin is specifically performed as follows: Step 1: Mix the glass fiber with 80% by mass sulfuric acid solution and 90% by mass nitric acid solution, and stir evenly to obtain a mixed solution; Step 2: Mix the mixed solution and acrylic resin, add anhydrous ethanol, and perform ultrasonic treatment at 400-700W for 1-2h; Step 3: Continue to add silane coupling agent and deionized water, stir at a speed of 200-500 rpm for 30-40 minutes, add pH adjuster to adjust the pH of the solution to 7-8, and obtain modified resin.
7. The smooth and soft-touch quartz stone plate according to claim 6, characterized in that: The weight ratio of the sulfuric acid solution to the nitric acid solution is 1:0.5-1; the weight ratio of the silane coupling agent to deionized water is 0.1-0.3:
1.
8. The smooth and soft-touch quartz stone plate according to claim 1, characterized in that: The ultra-high molecular weight polyethylene is produced by a melt spinning method; The melt spinning method is used to prepare ultra-high molecular weight polyethylene, and the specific operation process is as follows: Step 1: removing impurities from ultra-high molecular weight polyethylene powder; Step 2: After removing impurities, cool to 0-20°C, put into a melter, and melt polymerize at 200-300°C and 2-3MPa. Finally, extrude the melt through an extruder to obtain ultra-high molecular weight polyethylene.
9. A process for producing a quartz stone plate, which is used to produce a smooth and soft-touch quartz stone plate as claimed in any one of claims 1 to 8, characterized in that: The process comprises the following processing steps: S1: placing aluminum oxide into a processing device and applying high-frequency high-voltage electricity to cause corona discharge, and then adding ultra-high molecular weight polyethylene to obtain a mixture for standby use; S2: Mix quartz sand, quartz powder, modified resin, white slurry, curing agent and coupling agent, transfer to a pressing machine for pressing and molding, and then cure at a medium temperature of 80-120° C. to obtain a green body layer; S3: applying the mixture to the sheet material layer, coating the color slurry and filling the fine lines, and then performing low temperature curing treatment to obtain a cured material; S4 polishes the solidified material to obtain a quartz stone plate.
10. The manufacturing process of the quartz stone plate according to claim 9, characterized in that: The compression molding pressure is 20 to 50 MPa; The amount of the mixture applied to the sheet material is 280-300 g / m 2 The low temperature curing is carried out in a pipeline curing furnace, and the curing temperature is 75-85°C.